Policy on Balanced Regional Development in Macedonia-Goals, Challenges, Trends - Penev, Slagan; Trenovski, Borce (University Library of Munich, Germany, 2016)
According to data from official state institutions analyzed in the study, the policy on balanced regional development is facing serious challenges and is yet to engage in serious efforts in the future. Evidence on the unfavourable situation is found in data whereby more than half of investments continue to be generated in the most developed region, population growth in most regions is negative, while the three least developed regions (Northeast, Polog and Southwest) are facing high unemployment and have not improved their respective contribution shares in GDP in the last years compared with other regions in the state. In order to make regional development truly balanced, funding practices must adhere to the existing methodology or new methodology should be proposed for distribution of budget funds, according to which funds in the amount of 1% of GDP (or 3.25% as enlisted by the Government in one of its documents) will be awarded according to the relevant shares calculated on the basis of development in individual planning regions. Within the shortest deadline possible, the Council on Balanced Regional Development or the Ministry of Local Self-Government should establish a transparent reporting system on all parameters related to regional development, thus increasing interest and awareness of citizens for this important policy for the state’s future. Even the Strategy on Regional Development 2009-2019 refers to information system that would allow adherent compliance with the principles of transparency and accountability in strategy implementation, and would ensure access to public information related to strategy implementation. Having in mind that policy on balanced regional development is in compliance with strategic goal of the Republic of Macedonia in terms of its aspiration to join the EU, authors of this analysis believe that consensus is needed among main political actors for further and more committed implementation of the Law on Balanced Regional Development. Having in mind that this law and strategy had been adopted almost one decade ago and there is no visible progress in terms of awareness in society and in terms of political will, it seems as if the law does not exist. In spite of greater will and commitment demonstrated by management structures at relevant institutions and bodies toward capacity building for regional development, the possibility for establishment of special ministry of regional development should be reconsidered.